Optimal Strategies for Flood Prevention - Eijgenraam, Carel; Brekelmans, Ruud; den Hertog, Dick; Roos, Kees (Management Science, 2017)
Flood prevention policy is of major importance to the Netherlands since a large part of the country is below sea level and high water levels in rivers may also cause floods. In this paper we propose a dike height optimization model to determine economically efficient flood protection standards. We improve the model proposed by David van Dantzig [van Dantzig D (1956) Economic decision problems for flood prevention. Econometrica 24(3):276–287] after a devastating flood in the Netherlands in 1953. Our model is nonconvex, but we derive an explicit simple expression for the global optimal solution, which is periodic. We also discuss how to use this optimal investment policy to derive an efficient flood protection standard. The rather simple expression for this standard gives us much insight into how it depends on several relevant economic and climate model parameters. This approach has been applied to all dike rings in the Netherlands, and the resulting standards have been stated in the new Delta Programme 2015, which has been accepted by the government. This paper was accepted by Yinyu Ye, optimization.